The Effect of Low-Level Laser Therapy on Human Leukemic Cells - Dastanpour, Somayeh; Momen Beitollahi, Jalil; Saber, Kazem (Journal of Lasers in Medical Sciences, 2015)
Introduction: Laser phototherapy is used for the treatment of chemotherapy-induced oral mucositis in patients with leukemia, although there are limited data supporting the safety of this method. This study aimed to evaluate the effect of different doses of low-level laser on proliferation of acute myeloid leukemia (AML) cell line (KG-1a) in vitro. Methods: A plastic flask containing 5,000,000 KG-1a cultured cells was provided by Iran Pasteur Institute. KG-1a cell line has been produced from the bone marrow aspirate of a 59-year-old white male with acute myelogenous leukemia. Upon completion of the proliferation steps of KG-1a cell line, 7×104 cells were placed in 96-well tissue culture plates. All the surrounding wells were filled with Wright-Giemsa stain in order to prevent laser from scattering to the neighboring wells. In total, 28 plates were prepared using this method. After a forty-eight hours incubation period, irradiation was performed in continuous mode with an infrared laser of 810nm wavelength. After 24 hours, cells cultures were exposed to one, two, or three applications of laser irradiation. Irradiation exposures were performed at energy densities of 5, 10, and 20 J/cm2. Each experiment included 18 replicates for each application of laser and 6 replicates of negative/untreated controls. For experiments with two and three repeated exposures, the irradiation applications were separated by 48 hours. All the culture plates were incubated for seven days. Cell proliferation was evaluated using the MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assay after seven days. Spectroscopy (620nm) was used to determine the optical density (OD) of both irradiated and control samples. Results: Significant increase in cell proliferation was seen only after two exposures at energy density of 20J/cm2 (P=0.021). Conclusion: Although LLLT is commonly used to treat radiotherapy- or chemotherapy- induced mucositis, as long as further studies demonstrate that different wavelengths and doses of laser phototherapy are safe and effective in treatment of mucositis, clinicians should remain cautious regarding the use of this treatment modality to treat patients with malignancies.